Smoke toxicity effect of Artemisia Parviflora against dengue vector Aedes Aegypti Keywords: - R, Uma Devi; D, Lakshmi (Journal of Research in Biology, 2012)
Background and Objectives: This paper reports the smoke toxicity effect of Asteraceae plant species against the dengue vector, adult Aedes aegypti. These plants are used traditionally as source of medicine. Methods: The mosquito coils were prepared by using leaves, root, and the stem of Artemisia Parviflora by mixing with coconut shell and charcoal powder as burning material. Test mosquito coil were compared with commercially available coils. The percentage of unfed mosquitoes and % of population reduction was calculated. Results: Smoke emerged from the coil made up of leaves showed maximum protection 51% and population reduction was 83.8%.Contol II showed highest toxic effect and more population. The smoke from root and stem coils showed moderate amount of protection. Conclusion: The result suggested that the smoke toxic effect of Artemisia Parviflora affects the central nervous system and hence affects the neuroendocrine system to inhibit the hatchability of eggs and reduces the egg laying capacity as well the egg hatchability of the mosquitoes.